PENINGKATAN HASIL BELAJAR SISWA MENGGUNAKAN MODEL ROLE PLAYING DALAM MATA PELAJARAN BAHASA INDONESIA DI SDN 43 TALANG - Esis Winda; Nurhayati; Zulmasri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was motivated by the lack of enthusiasm among students during the learning process. The use of inappropriate learning models does not clarify the message content and can even confuse the students. Students will focus on things they find interesting, which leads to lower learning outcomes and fails to meet the KKTP of 75. The purpose of this research is to plan, carry out, and improve students' learning outcomes in the subject of Indonesian language using the role playing model for fourth-grade students at SDN 43 Talang.This research was conducted in two cycles, each consisting of planning, action, observation, and reflection. The subjects were seven fourth-grade students of SDN 43 Talang in the 2025/2026 academic year. Data were collected through written tests and observation sheets, then analyzed descriptively and quantitatively to determine the average score and percentage of classical learning completion. The results of the study showed that learning planning by compiling teaching modules, preparing observation sheets, and compiling role-playing models. The implementation of learning using the role-playing model was carried out in two cycles using the role-playing model, and that students' Indonesian language learning outcomes improved when using the role playing model. The average student scores increased from 65.7 in cycle I to 84.1 in cycle II. The percentage of students who successfully completed their learning outcomes in cycle I was 3 people (42.9%), which increased to 7 people (100%) in cycle II.